Light–matter interaction of single quantum emitters with dielectric nanostructures - Tjahjana, Liliana (2018)
Single quantum emitters are critical components for many future quantum information technologies. Novel active material systems have been developed and transitioned into engineering efforts at nanoscale. Here, we review recent progress of diverse quantum emitters and their optical properties, including fluorescent point defect in bulk and single nanocrystal, two-dimensional materials, and quantum dots (QDs). Remarkable progress has also been made in controlling spontaneous emission by utilizing the local density of optical states in dielectric photonic nanostructures. We focus on the enhanced light–matter interaction between the emitter and cavity, enabling the realization of efficient and fast single photon sources.